ANALISIS KOMODITAS UNGGULAN DI WILAYAH KESATUAN PENGELOLAAN HUTAN LINDUNG MODEL HULU SUNGAI SELATAN - Adnan Ardhana; Muhammad Abdul Qirom (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
The objective of the research is to identify which main commodity crops can be developed in three sub- districts, within KPHL Model Hulu Sungai Selatan. The research was carried out during July to December 2016 in three sub-districts, namely: Loksado; Padang Batung; and Telaga Langsat, located within Hulu Sungai Selatan, South Kalimantan. Primary data and secondary data were collected during this research. Secondary data, in the form of time series which includes forest product and horticultural commodities data (food crops, palawija crops, vegetables) during the period of 2011-2015, which refer from Statistics Indonesia (Central Bureau of Statistic). Location Quotient (LQ) and Shif Share Analysis (SSA) method were used to analyze the collected data during this research. The result showed that food crops commodity and food crops sub-sector which become the main commodities of sub-districts within Hulu Sungai Selatan KPHL were peanuts in Loksado sub-district, cassava and paddy in Padang Batung sub-district. For the vegetable sub-sector, there was no main vegetable commodity because it only comparative or competitive advantage. For plantation and forestry commodities, the main commodities in Loksado sub-district were rubber and candlenuts, while for Padang Batung sub-district was rubber plant.